SOSIALISASI PENGUATAN EKSISTENSI SUBAK MELALUI PENGENALAN ALAT PERTANIAN TRADISIONAL DI DESA PENATIH DANGIN PURI - I Made Sumada; I Gusti Putu Agung Widya Goca; Anak Agung Gde Raka; I Kadek Arik Sasandi; Ni Made Dwi Primadani; Luh Artha Kusuma Wati; Yudi Pramana Rochani; I Dewa Gde Mahesa Pradnyadinata; Recky Plangiten; Rendy Tama Prasetya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Subak survival in Bali is worrying. Land conversion has paralyzed the Subak irrigation system. Social changes and Bali's growing population have converted rice fields into housing, causing Subak to lose land for crops like rice. Subak plays a crucial role in reducing the rate of land conversion through the implementation of customary rules (awig-awig) and wise land management. In light of Subak's pivotal role, concerted socialization and educational initiatives are imperative to bolster its resilience. These efforts should encompass the reintroduction of traditional agricultural instruments to the community, with a particular focus on engaging the younger demographic. This activity is expected to raise awareness of the importance of preserving Subak as an integral part of Balinese culture and agriculture. It is anticipated that this PKM activity will effectively reinforce the values of Tri Hita Karana, the prevailing philosophy of Subak, thereby serving as a crucial foundation in addressing the challenges posed by modernization, climate change, and the shift in interest among the younger generation towards the agricultural sector. The socialization of traditional agricultural tools in Penatih Dangin Puri Village, Denpasar, involves the introduction of these tools and direct demonstrations and training from Subak members. This approach is expected to enhance Subak members' abilities to recognize, maintain, and utilize agricultural tools.